For a critical music education front of consumption and alienation (Revista NUPEART, 2021)
The general objective of this research is to understand how critical theory contributes to thinking about a more reflective and resistant music education in the face of consumption and alienation. We are based on some theories of resistance to the influence of the cultural industry and the search for an integral and humanistic musical formation in line with the ideas of a more autonomous society. Based on the studies of Theodor Adorno, and other authors linked to Critical Theory, we seek to contemplate the proposal to understand the relationship between music and consumption. In this way, an opinion poll was conducted with music teachers and students from a higher education institution to demonstrate points related to consumption, human training, and the importance of humanistic knowledge in music classes. The qualitative analysis of the data in this research was based on the following categories: consumption, alienation, resistance to the cultural industry, and training of music educators. Thus, we seek to understand how the elements of a critical formation can contribute to thinking about a more reflective and resistant musical education in the face of consumption and alienation.
Keywords: Music Education; Consumption; Cultural Industry